2020
DOI: 10.22487/aksioma.v9i2.520
|View full text |Cite
|
Sign up to set email alerts
|

Profil Pemahaman Konsep Siswa Ditinjau Dari Tingkat Kemampuan Matematika Pada Materi Fungsi Komposisi

Abstract: The aim of this research was to describe the profile of understanding the concept of class X MIA students based on the level of mathematical ability. The research was conducted at MA Alkhairaat Palu using a qualitative descriptive approach. The results of the study show that the understanding of the concept of ST in classifying the function of composition is that there is a function and operation of composition. Identify the characteristics of operations or concepts students use associative, distributive, comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Understanding of concepts can be influenced by several things, one of which is students' mathematical abilities. This is in accordance with the results of research by (Gani et al, 2020) which revealed that students have different abilities in understanding a mathematical concept. Therefore, it is very important for a teacher to know the ability of each student to understand the concepts being taught.…”
Section: Introductionsupporting
confidence: 92%
“…Understanding of concepts can be influenced by several things, one of which is students' mathematical abilities. This is in accordance with the results of research by (Gani et al, 2020) which revealed that students have different abilities in understanding a mathematical concept. Therefore, it is very important for a teacher to know the ability of each student to understand the concepts being taught.…”
Section: Introductionsupporting
confidence: 92%
“…This study aims to obtain a description or description of students' concept understanding of two-variable linear equation system material based on mathematical ability expressed through words or writing. Concept understanding profile in terms of mathematical ability (Gani, et al 2020) entitled the profile of students' concept understanding in terms of mathematical ability level. This is in line with research conducted by Sari, et al (2022) who analysed the ability to understand mathematical concepts of the material of the system of linear equations of two variables in terms of learning independence.…”
Section: Introductionmentioning
confidence: 99%